The use of nitrofurantoin for children with acute cystitis caused by extended-spectrum B-lactamase-producing Escherichia coli - Kara, A.; Gurgoze, M. K. (Elsevier Sci Ltd, 2019)
Background Acute cystitis in children caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (E. coli) is on the rise. Treatment of these is usually parenteral treatment. The aim of this study was to investigate the clinical and microbiological efficacy of oral nitrofurantoin treatment in children with lower urinary tract infection (UTI) caused by ESBL-producing E. coli. Methods Fifty children with lower UTI due to ESBL-producing E. coli were prospectively studied. Demographic data, clinical condition, laboratory values, treatment regimens, and complications of the patients were recorded. Urine samples were obtained by transurethral catheterization or clean catch; urine bags were not used for specimen collection for culture. Patients with lower UTI due to ESBL-producing E. coli and found to be susceptible to nitrofurantoin were given oral nitrofurantoin. Patients were re-evaluated 3-4 days after the end of treatment. Renal scintigraphy was performed 1-3 months after the end of treatment. Results A total of 50 pediatric patients (48 females and 2 males) were enrolled into study. The mean age was 7.5 +/- 3.96 years (range, 1-17 years). The duration of nitrofurantoin treatment was 10 days. Bacteriological response was observed in 49 of 50 patients (98%). No patient had symptoms after treatment. No significant side-effect was observed in any of the patients. All patients had normal serum creatinine values. Renal scintigraphic study, which was performed in all patients 1-3 months after completion of treatment, demonstrated the non-scarring in 48 of 50 patients (96%). Conclusions UTIs due to ESBL-producing E. coli are a serious problem because of the bacteria's multidrug antibiotic resistance pattern. This study suggests that oral nitrofurantoin treatment could be a good alternative for lower UTI caused by ESBL-producing E. coli in pediatric patients.
Keywords: Urinary tract infection; Escherichia coli; Extended-spectrum beta-lactamase; Nitrofurantoin; Children